Implementasi CSR (Corporate Social Responsibility) Bank Jatim Surabaya dalam Pengembangan UMKM (Usaha Mikro, Kecil, dan Menengah) di Jawa Timur - Reghita Priskilla Harlington; Binti Azizatun Nafi’ah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research investigates the implementation of Corporate Social Responsibility (CSR) by Bank Jatim Surabaya in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in East Java. The research method employed a qualitative approach with data collection techniques such as in-depth interviews and observations. The findings indicate that Bank Jatim has successfully complied with existing regulations and provided significant assistance to MSMEs. However, there are some shortcomings, particularly in the aspects of socialization and administrative procedures. In conclusion, the CSR program of Bank Jatim has a positive impact on the growth and sustainability of MSMEs in East Java.